Contribution of Social Science Electives to Engineering Students - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
Even though at first sight engineers are concerned solely with technology, they are superiors of a number of employees, whom they should handle wisely. Moreover, interactions with other units within the technical environment necessitate further human relations, as well. In that context, some familiarity with social sciences appear to be extremely useful for achievement in the field of engineering. Accordingly, social science electives should be encouraged in engineering faculties.
Keywords: Engineer; technical; social sciences; behavioral sciences